2009
DOI: 10.1038/eye.2009.16
|View full text |Cite
|
Sign up to set email alerts
|

Visual outcome after open globe injury: a comparison of two prognostic models—the Ocular Trauma Score and the Classification and Regression Tree

Abstract: Aims To compare the ocular trauma score (OTS) and the classification and regression tree (CART) as prognostic models of visual outcome after open globe injury. Methods A retrospective review of 100 consecutive open globe injuries at the Sunderland Eye Infirmary was conducted from January 1999 to December 2007. Univariate chi-square analysis was used to identify the variables associated with visual outcome. We compared the CART and OTS predictions with the actual visual outcomes and calculated the sensitivity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
72
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(81 citation statements)
references
References 20 publications
8
72
1
Order By: Relevance
“…Our outcomes are broadly in line with those originally reported by Kuhn Man and Steel, 7 with a non-significant difference in favour of CART.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our outcomes are broadly in line with those originally reported by Kuhn Man and Steel, 7 with a non-significant difference in favour of CART.…”
Section: Discussionsupporting
confidence: 81%
“…Sensitivity and specificity for OTS and CART were calculated for open-globe injuries as previously described. 7 McNemar w 2 -test was used to compare sensitivity and specificity measures of CART and OTS, as previously described. 8 P-values were 40.05 for all comparisons.…”
Section: Resultsmentioning
confidence: 99%
“…Using the OTS, 98.9% of eyes in the general population could be graded in a trauma room. Knyazer et al 35 report the prognostic value of the OTS in zone-3 open-globe injuries, and Man et al 36 found that the OTS and the CART had equal prognostic effectiveness in the general population.…”
Section: Discussionmentioning
confidence: 98%
“…17,19,23 This would be expected clinically as posterior segment injury can cause irreversible damage to the retina and optic nerve and thus carry a poor visual prognosis, even after the structural integrity of the globe has been repaired. 18 Children may develop more extensive postoperative inflammation, scarring, and proliferative retinopathy than adults, and these may affect anatomical and functional outcomes. 28,29 Retinal detachment develops in approximately 40% to 50% of eyes with posterior open globe injuries and is associated with a particularly poor prognosis.…”
Section: Discussionmentioning
confidence: 99%